1987
DOI: 10.1111/j.1559-1816.1987.tb00320.x
|View full text |Cite
|
Sign up to set email alerts
|

Getting More by Asking for Less: The Effects of Request Size on Donations of Charity1

Abstract: In the context of an annual fundraising drive for the American Society, two field experiments were conducted to test the relative effectiveness of suggesting either small or large contributions. In experiment 1, as part of a door‐to‐door campaign 300 people were randomly assigned to: (a) a standard request for contributions (control); (b) the standard request plus the words, “even a penny will help”; or (c) the standard request plus the words, “a generous contribution would really help.” As hypothesized, askin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 6 publications
2
76
2
Order By: Relevance
“…One such strategy is the argument that one 'cannot afford a donation'. Legitimising paltry contributions by adding the phrase 'every penny helps' or 'even a penny helps' in a solicitation for contributions may neutralise these strategies (Cialdini and Schroeder, 1976;Reingen, 1978;Brockner et al, 1984;Weyant and Smith, 1987;Doob and McLaughlin, 1989). When even a penny helps, one easily appears to be an unhelpful person if one does not donate, which makes it difficult to say no.…”
Section: Discussionmentioning
confidence: 99%
“…One such strategy is the argument that one 'cannot afford a donation'. Legitimising paltry contributions by adding the phrase 'every penny helps' or 'even a penny helps' in a solicitation for contributions may neutralise these strategies (Cialdini and Schroeder, 1976;Reingen, 1978;Brockner et al, 1984;Weyant and Smith, 1987;Doob and McLaughlin, 1989). When even a penny helps, one easily appears to be an unhelpful person if one does not donate, which makes it difficult to say no.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the amount requested may increase the amount donated if the amount requested is not perceived as excessive (Doob & McLaughlin 1989). However, one study found that a request for a "generous contribution" rather than a specific amount decreases the likelihood that a gift will be made in door-to-door solicitations (Weyant & Smith 1987). Desmet (1999) found a positive effect of asking for more on average donations in a direct mail campaign among irregular donors, but not among regular donors.…”
Section: (A) Costsmentioning
confidence: 99%
“…One such strategy is the argument that one "cannot afford a donation". Legitimizing paltry contributions by adding the phrase "Even a penny helps" in a solicitation for contributions may neutralize these strategies ( (Brockner et al 1984;Cialdini & Schroeder 1976;Doob & McLaughlin 1989;Reingen 1978;Weyant & Smith 1987). When even a penny helps, one easily appears to be an unhelpful person if one does not donate, which makes it difficult to say no.…”
Section: "Even a Penny Helps"mentioning
confidence: 99%
See 1 more Smart Citation
“…The lab experiments by Briers et al (2007) with 2 suggestions of 0.5€ or 3€ generates lower return as compared to no suggestion case. Weyant and Smith (1987) examine the effect of, both, smaller and larger suggestions.…”
Section: Literaturementioning
confidence: 99%